National Education Longitudinal Study, 1988 ([Verlag nicht ermittelbar], 1990)
This collection represents the first stage of a major longitudinal effort to provide trend data about critical transitions experienced by students as they leave elementary school and progress through high school and into college or their careers. The 1988 eighth-grade cohort will be followed at two-year intervals as this group passes through high school and postsecondary education. The longitudinal data collected will yield policy-relevant information about educational processes and outcomes, early and later predictors of dropping out, and students' access to programs and equal opportunity. The study has four types of data files. The Parent Component was designed to collect information about the factors that influence educational attainment and participation, including questions exploring family background and socioeconomic conditions and character of the home educational system. The School Administrator component was designed to gather general descriptive information about the educational settings in which the surveyed students were enrolled in the winter and spring of 1988. These data were collected from the chief administrator of each base-year school and concern school characteristics, grading and testing structure, school culture and academic climate, program and facilities information, parental interactions and involvement, and teaching staff characteristics. The Student Component collected information on school work, aspirations, social relationships, and basic achievement areas such as reading, mathematics, science, and social studies. The Teacher Component provided data that could be used to analyze the behaviors and outcomes of the student sample. Teachers were surveyed about the base-year students' characteristics and performance in the classroom, curriculum and classes for eighth graders, and teacher demographics, professional characteristics, and relationships with other teachers, students, and parents.